Enzymes-based resistant mechanism in pyrethroid resistant and susceptible Aedes aegypti strains from northern Thailand - Somwang P. (2014)
Previous studies have shown that permethrin resistance in our selected PMD-R strain of Aedes aegypti from Chiang Mai, Thailand, was associated with a homozygous mutation in the knockdown resistance (kdr) gene and other mechanisms. In this study, we investigated the metabolic mechanism of resistance of this strain compared to the PMD strain which is susceptible to permethrin. The permethrin susceptibility of larvae was determined by a dose-response bioassay. Two synergists, namely piperonyl butoxide (PBO) and bis(4-nitrophenyl)-phosphate (BNPP), were also added to determine if the resistance is conferred by oxidase or esterase enzymes, respectively. The LC50 value for PMD-R (25.42 ppb) was ∼25-fold higher than for PMD (1.02 ppb). The LC50 was reduced 3.03-fold in PMD-R and 2.27-fold in PMD when the oxidase inhibitor (PBO) was added, but little or no reduction was observed in the presence of BNPP, indicating that oxidative enzymes play an important role in resistance. However, the LC50 previously observed in the heterozygous mutation form was reduced ∼eightfold, indicating that metabolic resistance is inferior to kdr. The levels of cytochrome P450 (P450) extracted from fourth instar larvae were similar in both strains and were about 2.3-fold greater in microsomal fractions than in crude supernatant and cytosol fractions. Microsome oxidase activities were determined by incubation with each of three substrates, i.e., permethrin, phenoxybenzyl alcohol (PBOH), and phenoxybenzaldehyde (PBCHO), in the presence or absence of nicotinamide adenine dinucleotide phosphate (NADPH), nicotinamide adenine dinucleotide (NAD+), PBO, and BNPP. It is known that hydrolysis of permethrin produces PBOH which is further oxidized to PBCHO by alcohol dehydrogenase (ADH) and then to phenoxybenzoic acid (PBCOOH) by aldehyde dehydrogenase (ALDH). When incubated with permethrin, a small amount of PBCOOH was detected in both strains (about 1.1-1.2 nmol/min/mg protein), regardless of the addition of NADPH. The addition of PBO resulted in about 70% and 50% reduction of PBCOOH in PMD and PMD-R, respectively. The addition of BNPP reduced PBCOOH about 50% and 35% in PMD and PMD-R, respectively. Using PBOH as substrate increased PBCOOH ∼16-fold and ∼40-fold in PMD and PMD-R, respectively. Using PBCHO as substrate increased PBCOOH ∼26-fold and ∼50-fold in PMD and PMD-R, respectively. The addition of NADPH, and particularly NAD+, increased the level of PBCOOH. Together, the results have indicated the presence of a metabolic metabolism involving P450, ADHs, and ALDHs in both PMD and PMD-R strains, with greater enzyme activity in the latter. © 2011 Springer-Verlag.